Multisite chronic pain and the risk of autoimmune diseases: A Mendelian randomization study - Tang, Yidan; Liu, Weizhi; Kong, Weishuang; Zhang, Shuangyi; Zhu, Tao (Frontiers in Immunology, 2023)
Background: Accumulating evidence has demonstrated that an association between chronic pain and autoimmune diseases (AIDs). Nevertheless, it is unclear whether these associations refer to a causal relationship. We used a two-sample Mendelian randomization (MR) method to determine the causal relationship between chronic pain and AIDs. Methods: We assessed genome-wide association study (GWAS) summary statistics for chronic pain [multisite chronic pain (MCP) and chronic widespread pain (CWP)], and eight common AIDs, namely, amyotrophic lateral sclerosis (ALS), celiac disease (CeD), inflammatory bowel disease (IBD), multiple sclerosis (MS), rheumatoid arthritis (RA), systemic lupus Erythematosus (SLE), type 1 diabetes (T1D) and psoriasis. Summary statistics data were from publicly available and relatively large-scale GWAS meta-analyses to date. The two-sample MR analyses were first performed to identify the causal effect of chronic pain on AIDs. The two-step MR and multivariable MR were used to determine if mediators (BMI and smoking) causally mediated any connection and to estimate the proportion of the association mediated by these factors combined. Results: With the utilization of MR analysis, multisite chronic pain was associated with a higher risk of MS [odds ratio (OR) = 1.59, 95% confidence interval (CI) = 1.01-2.49, P = 0.044] and RA (OR = 1.72, 95% CI = 1.06-2.77, P = 0.028). However, multisite chronic pain had no significant effect on ALS (OR = 1.26, 95% CI = 0.92-1.71, P = 0.150), CeD (OR = 0.24, 95% CI = 0.02-3.64, P = 0.303), IBD (OR = 0.46, 95% CI = 0.09-2.27, P = 0.338), SLE (OR = 1.78, 95% CI = 0.82-3.88, P = 0.144), T1D (OR = 1.15, 95% CI = 0.65-2.02, P = 0.627) or Psoriasis (OR = 1.59, 95% CI = 0.22-11.26, P = 0.644). We also found positive causal effects of MCP on BMI and causal effects of BMI on MS and RA. Moreover, there were no causal connections between genetically predicted chronic widespread pain and the risk of most types of AIDs disease. Conclusion: Our MR analysis implied a causal relationship between MCP and MS/RA, and the effect of MCP on MS and RA may be partially mediated by BMI.